Phase composition, microstructure and thermophysical properties of the Srx(Zr0.9Y0.05Yb0.05)O1.95+x ceramics. Issue 4 (April 2021) - Ma, Wen; Gao, Yuanming; Zhang, Jingxin; Bai, Yu; Jia, Ruiling; Dong, Hongying; Wang, Ruijun; Bao, Manyu
Abstract: Srx (Zr0.9 Y0.05 Yb0.05 )O1.95+x (x=1.0, 0.9, 0.8, 0.7) ceramics were prepared by solid state reaction sintering. The sintered Sr1.0 (Zr0.9 Y0.05 Yb0.05 )O2.95 is a single-phase solid solution while the sintered Srx (Zr0.9 Y0.05 Yb0.05 )O1.95+x (x=0.9−0.7) are composites, and a significant grain growth inhibition is observed in the sintered Srx (Zr0.9 Y0.05 Yb0.05 )O1.95+x (x=1.0, 0.9). Rare-earth elements distribution in the bulk materials indicates that Yb and Y preferentially substitute Zr-sites in SrZrO3, and the highest solubility of RE2 O3 in pure SrZrO3 is ∼0.8 mol%. The sintered Srx (Zr0.9 Y0.05 Yb0.05 )O1.95+x have high thermal expansion coefficients up to ∼11.0×10 −6 K -1 (1200°C). Sr0.8 (Zr0.9 Y0.05 Yb0.05 )O2.75 has the lowest thermal conductivity of 1.38 W·m -1 ·K -1 at 800°C. Srx (Zr0.9 Y0.05 Yb0.05 )O1.95+x (x=1.0, 0.9, 0.8) show no phase transition from 600 to 1400°C, whereas Srx (Zr0.9 Y0.05 Yb0.05 )O1.95+x (x=0.9, 0.8) have excellent high-temperature phase stability over the whole investigated temperature range. Therefore, Srx (Zr0.9 Y0.05 Yb0.05 )O1.95+ x (x=1.0, 0.9, 0.8) are considered as promising TBCs materials that might be operated at higher temperatures compared to YSZ.